Simple visualization of fish migration history based on high‐resolution otolith δ18O profiles and hydrodynamic models - Tatsuya Sakamoto (Limnology and Oceanography Letters)
Abstract Oxygen‐stable isotope (δ18O) in otoliths has been useful to infer marine fish migrations. However, because otolith δ18O is affected by two parameters, temperature and δ18O of ambient water, its interpretation becomes challenging when neither of them is constant. Here, I describe a simple method using hydrodynamic models to visualize potential migration histories from high‐resolution otolith δ18O chronologies. By predicting the distribution of potential otolith δ18O, that is, otolith δ18O isoscape from modeled temperature and salinity distributions and comparing these with observed values, possible fish locations can be inferred. The demonstration of sardine juveniles in the western North Pacific region reproduced their seasonal northward migrations accurately. The predicted locations were consistent with the results of sampling surveys of eggs and juveniles and correctly approached the point where fish were caught. The methodological recommendations and the successful demonstration in this study may help in planning future sclerochronology research using carbonate δ18O values.